Normal Coordinate Analysis of 5-Carbethoxy-2-thiouracil - BALACHANDRAN*, V.; ARIVAZHAGAN, M.; MURUGAN, M. (Asian Journal of Chemistry, 2009)
Normal coordinate analysis of fundamental vibrations of 5-carbethoxy-2-thiouracil has been carried out by assuming Cs point group symmetry. The potential energy constants are obtained by applying Wilson's FG matrix method. All the modes of vibrations are assigned and the potential energy distribution calculations are performed.